1988
DOI: 10.1111/j.1471-4159.1988.tb02998.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neurotensin Binding Sites in Intact and Solubilized Bovine Brain Membranes

Abstract: Analysis of the equilibrium binding of [3H]-neurotensin(1-13) at 25 degrees C to its receptor sites in bovine cortex membranes indicated a single population of sites with an apparent equilibrium dissociation constant (KD) of 3.3 nM and a density (Bmax) of 350 fmol/mg protein (Hill coefficient nH = 0.97). Kinetic dissociation studies revealed the presence of a second class of sites comprising less than 10% of the total. KD values of 0.3 and 2.0 nM were obtained for the higher and lower affinity classes of sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The apparent increase in molecular mass of TC II-R due to disulfide bond disruption noted in this study is not a unique situation. Other receptors such as the cation-independent mannose 6-phosphate receptor (27), neurotensin receptor (28), and ␤-adrenergic receptor (29) behave similarly on nonreducing SDS-PAGE following their reductive alkylation.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent increase in molecular mass of TC II-R due to disulfide bond disruption noted in this study is not a unique situation. Other receptors such as the cation-independent mannose 6-phosphate receptor (27), neurotensin receptor (28), and ␤-adrenergic receptor (29) behave similarly on nonreducing SDS-PAGE following their reductive alkylation.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical and pharmacological properties of these binding sites have been extensively studied using mammalian brain homogenates as well as membrane preparations from neuronal and certain non-neuronal cell lines [5,6]. It has been shown that the interaction with these receptors modulates intracellular levels of cGMP, CAMP and inositol phosphates [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Our (Ahmad et al, 1987). In canine intestinal smooth muscle as well as rat (Mazella et al, 1983) and bovine brain (Mills et al, 1988 we observed in the circular muscle may suggest occuancy of a low-affinity receptor, but resolution of such row-affinity binding sites must await further studies using higher concentrations of [lZ5I]-NT. Nevertheless, the consistency of our estimates with those of others for a high-affinity binding site for NT is noteworthy, since our experiments were conducted in a physiological medium.…”
Section: Discussionmentioning
confidence: 59%